Bacterial Causes Tonsillitis in Children, Study the Resistance to Antimicrobials and the Effect of Clove Extracts on Selected Isolated Bacteria. (Baghdad Science Journal, 2013)
In this study Isolated Pathogenic bacteria which causes Tonsillitis in Children with ages between 3-17 years. They are admitted to Central Children Hospital (Al-Karch) and Ebn-Albalady Hospital (Al-Rusafa). 200 cases were collected which include 120 Male and 80 Female. The result of the recent study shows that the isolation percentage was 40% from Male and 35% from Female. In this study Fifty six isolated were Identified, 20 were ?-hemolytic Streptococcus which was Streptococcus pyogenes, formed (36%) from all isolated.6 Pathogenic bacteria were ?- hemolytic Streptococcus which was Streptococcus pneumoniae formed (11%). The number of Moraxella catarrhalis bacteria was 12 formed (21%), the number of Haemophilus influenzae was 10 formed (18%).Whereas the number of Staphylococcus aureus was 8 formed (14%). The Antimicrobial Susceptility test to commonly used Antimicrobial shows that the most isolate Bacteria were sensitive to Antimicrobial ( AMC and CEP ) and Resistance to ( P and E ) with some exception. The Antimicrobial Susceptility test of Staphylococcus aureus to Oxacillin showed the predominant of Oxacillin-Sensitive S. aureus (OSSA) which form 88% whereas the percentage of Oxacillin -Resistant S. aureus (ORSA) was 12%. The effect of crude aqueous and solvent extracts of clove on selected isolated bacteria. Shows the efficiency of clove extracts which gives the biggest inhibition zones by all extracts with efficacy of methanol extract compared with the other solvents extracts. The inhibition zone was 25.2 mm fore Streptococcus pyogenes and the MIC wasMIC was 75?g/ml. 25.6 mm 75?g/ml. 24.8 mm for Streptococcus pneumoniae and For Staphylococcus aureus and MIC was 50?g/ml, whereas the inhibition zone was 22.2 mm and 22.1 mm for Moraxella catarrhalis and Haemophilus influenza respectively and the MIC was 100?g/ml.